2019
DOI: 10.3390/rel11010001
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia’s Orphanage Trade: Islamic Philanthropy’s Good Intentions, Some Not So Good Outcomes

Abstract: In 2011, Indonesia commenced an orphanage deinstitutionalization strategy known as the paradigm change in child protection. The strategy responded to human rights protocols emphasizing institutional care of children as a last resort. Orphanage based social workers were trained by the Ministry of Social Affairs (MOSA) to implement the paradigm change, increase parenting capacity and strengthen local supports to enable children’s reunification with their families. The paradigm change intended to reduce children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The civil service pay structure incentivised outreach recruitment missions focused on bringing children from families in poverty into care, as opposed to remunerating work towards the Paradigm Change. As in other research (Isimoya et al, 2018;Kang and Shen, 2017;McLaren and Qonita, 2020;Wang et al, 2018), incentive pay was found to motivate individuals to prioritise work on the basis of effort versus outcomes for them. Incentivisation in social work and administration presents risks to social justice and fairness, especially when (1) incentivisation is misaligned with welfare priorities or change agendas, and (2) when earning incentives are prioritised over value-based social work (Austin, 2013;Loyalka et al, 2019;Santibañez, 2020).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The civil service pay structure incentivised outreach recruitment missions focused on bringing children from families in poverty into care, as opposed to remunerating work towards the Paradigm Change. As in other research (Isimoya et al, 2018;Kang and Shen, 2017;McLaren and Qonita, 2020;Wang et al, 2018), incentive pay was found to motivate individuals to prioritise work on the basis of effort versus outcomes for them. Incentivisation in social work and administration presents risks to social justice and fairness, especially when (1) incentivisation is misaligned with welfare priorities or change agendas, and (2) when earning incentives are prioritised over value-based social work (Austin, 2013;Loyalka et al, 2019;Santibañez, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…The low base pay of social workers in Indonesia is influential in sustaining administrative prioritising based on the monetary rewards attached (McLaren and Qonita, 2020). Since the introduction of the Paradigm Change, incentivisation has not been applied to the wages of civil service orphanage-based social workers to prioritise the deinstitutionalisation of children, reunification, home visits and strengthening communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Muslim families and communities, connection to religion is important, but the complexities of multicultural relations can present challenges for health and welfare providers, and for Muslim-minorities (Amri and Bemak 2013;McLaren and Patil 2016;McLaren and Qonita 2020;Patil and McLaren 2019;Salma and Salami 2020). Several authors have attempted to unpack this complexity and its associations with lived experiences, such as of isolation and loneliness (Nagle 2016;Parati 2017), mental and physical ill-health (Koerner and Pillay 2020;McCoy et al 2016), and with general wellbeing or quality of life (Colic-Peisker 2009;Gardner et al 2014).…”
Section: Introductionmentioning
confidence: 99%